Characterization of Black Pigmenturia in a Cat with Apocrine Gland Cystadenocarcinoma. (April 2020) - Fournier, Q.; Höhn, A.; Deubel, S.; Milne, E.; Bavcar, S.; Morrison, L.
Summary: An 8-year-old neutered female domestic shorthair cat was presented for further management of an apocrine gland cystadenocarcinoma. Extensive nodal metastasis was diagnosed and the cat was humanely destroyed 2 months after presentation. Post-mortem histopathology of the cystadenocarcinoma revealed areas of yellow–brown granular pigmentation on light microscopy, staining positively for reducing substances with Schmorl's stain and demonstrating autofluorescence on confocal microscopy. The cat's urine was black and also exhibited autofluorescence, and further analysis revealed increased free pentosidine. Based on these findings, it was presumed that the apocrine gland cystadenocarcinoma was producing lipofuscin-like pigments and that the characteristics of the urine were at least partially secondary to advanced glycation end-products.